2020
DOI: 10.29259/ja.v14i1.10718
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Deteksi Fenomena Flypaper Effect Pada Kinerja Keuangan Kota Bengkulu

Abstract: The purpose of this research is to know the possibility of flypaper effect on Financial Performance of Bengkulu City by knowing the influence of locally-generated revenue (PAD), General Allocation Fund (DAU) to Bengkulu City. This reaseach used the time series data about the Budget Realization Report (LRA) of Bengkulu City and the Financial Statistics of Bengkulu Province which provided by the Central Bureau of Statistics of Bengkulu Province. Data analysis tool used is multiple regression analysis.The empiric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
(3 reference statements)
0
0
0
Order By: Relevance
“…Most of the sources of regional revenue in districts/city in Bengkulu Province still come from the balance fund (transfer) consisting of tax revenue sharing, non-tax/natural resources profit sharing, GAF and SAF and other revenues consisting of grant income, emergency fund income and other income. This is in line with the results of research bySeptriani et al (2020) which found that funds is obtained from general allocation funds (GAF). Meanwhile, the Special Allocation Fund (SAF) also has an important role in increasing regional revenues.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Most of the sources of regional revenue in districts/city in Bengkulu Province still come from the balance fund (transfer) consisting of tax revenue sharing, non-tax/natural resources profit sharing, GAF and SAF and other revenues consisting of grant income, emergency fund income and other income. This is in line with the results of research bySeptriani et al (2020) which found that funds is obtained from general allocation funds (GAF). Meanwhile, the Special Allocation Fund (SAF) also has an important role in increasing regional revenues.…”
supporting
confidence: 89%
“…Therefore, to achieve development targets, the local government of districts/cities in Bengkulu Province strives to improve the quality of Regional Expenditure to more productive expenditures, such as capital expenditure. Meanwhile, non-priorities such as spending on goods and subsidies must be right on target.The results of this research are in line with the results of research conducted bySeptriani, et al (2020) which found that General Allocation Fund (GAF) has a positive effect on Regional Expenditure in Bengkulu City. Where the amount of regional expenditure in Bengkulu City is largely determined by the amount of General Allocation Fund (GAF) received by the Bengkulu City government.…”
supporting
confidence: 88%